Service Trust, Loyalty, and Satisfaction: Do Clients Prefer Insurance Firms or Agencies? Evidence from Turkey - Acikdilli, Gaye; Bugra Soylu, Abdullah (Copernican Journal of Finance & Accounting, 2024)
Insurance services are based on trust. Customers’ trust is limited to assessing companies and agents. Providers measure trust, loyalty, and satisfaction of clients who had claims under their insurance policies. Structural Equation Modeling was used to evaluate relationships between insurance agencies, companies, and consumer loyalty using the SERVQUAL scale. A survey of the Turkish insurance marketplace reveals that service quality, customer satisfaction, and trust in the agency and insurance companies have significant effects on loyalty. Moreover, Turkish customers’ trust reveals greater loyalty to the individual agency than to insurance firms.